52. BrMPANEL: A PUBLIC RESOURCE OF ORGANOTROPIC CELL LINES. (4th August 2020) - Valiente, Manuel; Van Swearingen, Amanda; Anders, Carey; Bairoch, Amos; Boire, Adrienne; Bos, Paula; Cittelly, Diana; Erez, Neta; Ferrarro, Gino; Fukumura, Dai; Gril, Brunilde; Herlyn, Meenhard; et al.
Abstract: Central nervous system (CNS), notably brain, metastases are most prevalent in lung cancer (20–56% of patients), breast cancer (5–20%) and melanoma (7–16%). Lesions occur in both the brain parenchyma and the meninges. To mechanistically understand CNS metastasis formation and develop preventive and therapeutic strategies, it is essential to use model systems that, as much as possible, faithfully recapitulate the clinical disease process. Furthermore, the complexities of brain metastases dictate that studies should utilize multiple model systems in various stages of brain metastases progression. To facilitate brain metastasis research, 19 laboratories around the world have compiled comprehensive information on their brain metastasis mouse models. Each lab has provided details on the cell lines that they have generated or characterized as being capable of forming metastatic colonies in the brain, as well as principle methodologies of brain metastasis research. This Brain Metastasis Cell Lines Panel (BrMPanel, https://apps.cnio.es/app/BrainMetastasis/CellLines ) represents the first of its class and includes information about each cell line, how tropism to the brain was established, and the behavior of each model in vivo . The BrMPanel is composed of 60 cell lines, derived from patients (32 cell lines, 53%), mouse (27, 45%) or rat (1, 2%), and represent the three main cancer types that result in brain metastasis: breast cancer (38 cell lines, 63%), lung cancer (8, 13%) and melanoma (14, 23%). This resource is intended to assist investigators in choosing the most suitable model for research on brain metastasis, and is available to the entire scientific community. The ultimate goal of this effort is to facilitate research on this unmet clinical need, to improve models through a collaborative environment, and to promote the exchange of information on these valuable resources. We invite other collaborators to contribute their models to the BrMPanel to grow this resource.